2020
DOI: 10.48550/arxiv.2007.07906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An alternative to the Teukolsky equation

Yasuyuki Hatsuda

Abstract: We conjecture a new ordinary differential equation exactly isospectral to the radial component of the homogeneous Teukolsky equation. Surprisingly our equation looks much simpler than Teukolsky's one. We find this novel relation by a hidden symmetry implied from a four-dimensional N = 2 supersymmetric quantum chromodynamics. Our proposal is powerful both in analytical and in numerical studies. As an application, we derive high-order perturbative series of quasinormal mode frequencies in the slowly rotating lim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This perspective has been analyzed in the context of black hole physics in [21,22,23] where it was suggested that some physical properties of black holes, such as their greybody factor and quasinormal modes, can be studied in a particular regime in terms of Painlevé equations. A decisive step forward about the quasinormal mode problem has been taken in [24], where a different approach making use of the Seiberg-Witten quantum curve of an appropriate supersymmetric gauge theory has been advocated to justify their sprectrum and whose evidence was also supported by comparison with numerical analysis of the gravitational equation (see also [25,26] for further developments). This view point has been further analysed in [27], where the context is widely generalized to D-branes and other types of gravitational backgrounds in various dimensions.…”
Section: Introduction and Outlookmentioning
confidence: 99%
“…This perspective has been analyzed in the context of black hole physics in [21,22,23] where it was suggested that some physical properties of black holes, such as their greybody factor and quasinormal modes, can be studied in a particular regime in terms of Painlevé equations. A decisive step forward about the quasinormal mode problem has been taken in [24], where a different approach making use of the Seiberg-Witten quantum curve of an appropriate supersymmetric gauge theory has been advocated to justify their sprectrum and whose evidence was also supported by comparison with numerical analysis of the gravitational equation (see also [25,26] for further developments). This view point has been further analysed in [27], where the context is widely generalized to D-branes and other types of gravitational backgrounds in various dimensions.…”
Section: Introduction and Outlookmentioning
confidence: 99%
“…We have obtained the differential equation (3.21), which is also reduced to the Regge-Wheeler equation in the limit a → 0 as the (Chandrasekhar-)Detweiler and the Sasaki-Nakamura equations are. The extension to the case of different spins (the scalar waves and the electromagnetic waves) [26,27,28] and the explicit comparison of the quasi normal modes [15,16,22,29,30,31,32] would also be interesting.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…As well as in the Regge-Wheeler and the Teukolsky equations, the (confluent) Heun's equation also appears in the quantization of the Seiberg-Witten curves in supersymmetric gauge theories. For example in N = 2 supersymmetric SU(2) gauge theory coupled with three matter hypermultiplets in the fundamental representation of the gauge group, the quantum Seiberg-Witten geometry gives the following differential equation [19,21,15,16,22]…”
Section: Comparison With Quantum Seiberg-witten Geometrymentioning
confidence: 99%
See 2 more Smart Citations